Kuala Kubu Bharu, nature's playground / Siti Hazurah Indera Putera - Indera Putera, Siti Hazurah (UiTM Cawangan Negeri Sembilan, 2023)
A while ago I had a doctor's appointment scheduled in Kuala Lumpur. Traveling from Johor, I decided to spend the weekend ahead of my doctor's appointment in Kuala Kubu Bharu, Selangor. I have driven through this quiet and charming town many times before, but never had the opportunity to experience the area myself. Kuala Kubu Bharu is in the district of Hulu Selangor, with a land area of approximately 177 hectares and, a population of about 195 thousand people. With its network of rivers, waterfalls, rugged landscape, forests, and the nearby Fraser's Hill, Kuala Kubu Bharu is fast becoming the hub for nature lovers looking to escape their hectic life. Ramblers and hikers would prefer a walk or climb in the forest while others would visit the school of Kelah (Mahseer) fish at the Sungai Chiling fish sanctuary.